TINGKAT MOTIVASI PADA EKSTRAKURIKULER BOLABASKET SMAN 1 KEDONDONG - Dicky Hermawan; Reza Adhi Nugroho (Universitas Teknokrat Indonesia, 2023)
This study examines the basketball extracurricular motivation of SMAN 1 Kedondong based on intrinsic and extrinsic factors. The purpose of this study was to find out how big the level of student motivation in participating in basketball extracurricular activities. This type of research is descriptive quantitative with the research method used is a survey. The data collection instrument in this study used a questionnaire with a Likert scale. The population in this study was 30 students of basketball extracurricular at SMAN 1 Kedondong. Thus, the sample used was total sampling technique so that in this study the sample was taken with a total population of 30 students of basketball extracurricular at SMAN 1 Kedondong. The data analysis technique in this research is statistical descriptive analysis which is presented in percentage form. The results showed that the motivation for extracurricular basketball at SMAN 1 Kedondong was classified as good as many as 13 respondents (43.33%), but in terms of intrinsic factors, 12 respondents (40%) had a poor category, while on extrinsic factors there were 20 respondents ( 66.67%) has a very good category.